A Decade of Green Economic Literature: An Analysis-Based Bibliometric - Alqudah, Hamza; Al-Qudah, Mohammad; Huson, Yazan Abu; Lutfi, Abdalwali; Alrawad, Mahmaod; Almaiah, Mohammed Amin (International Journal of Energy Economics and Policy, 2024)
This research significantly contributes to comprehending the body of work surrounding green economics and sustainable economies by methodically reviewing and categorizing papers from the Web of Science (WoS) core collection. It highlights key authors, subjects, publishing sources, and nations relevant to green economic studies by meticulously analyzing 4,157 papers. Additionally, it constructs detailed visual maps based on referenced sources. By conducting a thorough bibliometric analysis, this study underscores the importance of using such tools to gauge research impact and productivity. Leveraging the WoS Core Collection, particularly the Science Citation Index Expanded and the Social Sciences Citation Index, was deliberate to ensure a comprehensive evaluation of green economic research. The data accentuates the changing landscape of this field, indicating its growing significance and the expanding academic discussions around sustainable economic practices. The research delves into emerging research directions that could inform considerations for a sustainable economy. Despite the marked increase in publications in recent years, signaling heightened interest in green economics and sustainable economy studies, this field remains in its infancy, with limited quantitative studies conducted. Consequently, many findings remain inconclusive, and numerous aspects in literature remain unexplored. Finally, this study outlines both practical and theoretical implications gleaned from its findings.